Safety and tolerability of Tilt Testing and Carotid Sinus Massage in the octogenarians - Kenny, Rose (My University, 2016)
Objective: to evaluate the safety and tolerability of Tilt Testing (TT) and Carotid Sinus Massage (CSM) in octogenarians with unexplained syncope. Methods: patients consecutively referred for transient loss of consciousness to the ‘Syncope Units’ of three hospitals were enrolled. TT and CSM were performed according to the European Society of Cardiology guidelines on syncope. Complications were evaluated in each group. An early interruption of TT was defined as ‘intolerance’ and considered as a non-diagnostic response. Results: one thousand four hundred and one patients were enrolled (mean age 72 ± 16 years, male 40.8%). Six hundred and ninety-four patients (49.5%) were 80 years old or older (mean age 83 ± 3 years) and 707 (50.5%) were younger (mean age 60 ± 17 years). Complications after TT occurred in 4.5% of older patients and in 2.1% of the younger ones (P = 0.01). All complications were ‘minor/moderate’, as prolonged hypotension, observed in ∼3% of patients ≥80 years. Major complications such as sustained ventricular tachycardia, ventricular fibrillation, asystole requiring cardiac massage, transient ischaemic attack, stroke and death were not observed in any patient. The presence of orthostatic hypotension and the mean number of syncopal episodes were predictors of TT complications. Intolerance was reported in 2.4% of older patients and 1% of the younger ones (P = 0.08), mainly due to orthostatic intolerance. No complications occurred after CSM. Conclusions: TT and CSM appear to be safe and well tolerated in octogenarians, who should not be excluded by age from the diagnostic work-up of syncope.
PUBLISHED
Cited By :1 Export Date: 6 January 2017
Keywords: Tilt Testing (TT) and Carotid Sinus Massage (CSM); Tilt Testing (TT) and Carotid Sinus Massage (CSM); Ageing